ANALISIS STRATEGI PEMASARAN PRODUK QORDH DALAM MENINGKATKAN EKONOMI MASYARAKAT DI KSPS BMT-UGT SIDOGIRI CAPEM JANGKAR SITUBONDO - Budi Sufyanto (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2020)
BMT (baitul mal wat tamwil) is a microfinance institution that operates on the basis of Islamic law principles and its activities do not charge interest or pay interest to customers. Rewards received by BMT and paid to customers depend on the agreement between the customer and the BMT. The agreement contained in BMT-UGT Sidogiri Capem Jangkar must comply with Islamic law, both terms and conditions of the contract that must be fulfilled. Based on the results of research and discussion, it is known that: first BMT-UGT Sidogiri Capem Jangkar in marketing products through several forms of promotional strategies, namely; Service promotion strategy, sales promotion, publicity promotion and advertising promotion. The two impacts felt by customers in the application of qordh product marketing had a very positive impact, namely; customers feel very benefited, there is no element of pressure from the BMT cooperative, it can encourage customer loyalty, provide a good basis for repeat purchases, customers feel helped, create a harmonious relationship between the company and customers.